Unpacking teachers’ beliefs about creative teaching in China higher education context - Han, Weijing; Abd Rahim, Nur Aira; Liu, Xuefei (Universiti Putra Malaysia, 2024)
In recent years, the concept of creativity has garnered increasing attention within the field of education. Educators are increasingly recognizing the pivotal role that teachers’ creative teaching plays in fostering innovative teaching practices, enhancing student engagement, and ultimately, improving educational outcomes. As such, understanding the nature and manifestations of creative teaching has become a topic of significant interest and importance in educational research. Despite its recognized importance, the concept of creative teaching remains multifaceted and complex, encompassing a range of cognitive, affective, and behavioral dimensions. The aim of this study was to investigate the essence of creative teaching through an examination of teachers’ practices. Guided by this objective, two primary research inquiries were formulated: (1) What are the underlying beliefs held by teachers regarding creative teaching? (2) How do teachers conceptualize the parameters of creative teaching? To explore these inquiries, a qualitative approach was employed as the methodological framework. Participants consisted of 14 teachers from a private university in China, chosen purposively for their firsthand experiences and insights into the phenomenon under investigation. The study revealed that teachers’ comprehension and formulation of creative teaching predominantly revolved around three orientations: teaching mode-oriented, teaching objective-oriented, and student-oriented approaches. Drawing from these research findings, the study discussed implications for the advancement and implementation of creative teaching among higher education instructors. Primarily, the study offers a platform for teachers to engage in reflective practices and gain insights into creative teaching from multifaceted perspectives and its underlying mechanisms, thereby fostering a more comprehensive grasp of the concept. Additionally, it is envisaged that the findings will contribute to the broader community of teacher educators, enabling them to deepen their understanding of creative teaching through shared experiences, thereby facilitating more effective implementation and fostering the high-quality development of creative teaching practices.